Improving the English Skills by Using Microsoft Office in the Learning Process for Management Informatics Students - Pujiastuti, Eka; Erniyati, Yelni; Haryono; Ulum, Bahrul (ETERNAL (English Teaching Journal), 2024)
Information and communication high technology in the world of education can be given in numerous disparate forms turn on cast their votes function. Microsoft department exists as a form of information and communication technology, big-name software that can be used in the process of learning English. The purpose of this activity is to help students better understand the features provided by Microsoft Office, including the Microsoft Word application (integrating between EndNote and Word for writing citations and references) and PowerPoint (Making a video). Deplorably, the continuous online course has brought almost various challenges within the domain of instruction, including both the substance being instructed and the guidelines instruments utilized, eventually driving decay in learning results. This emphasizes the creation of Microsoft Office-based advanced assets for instructive purposes, which are at that point included within the learning preparation. The technique utilized in this think about was investigation and advancement. The media improvement handle utilized the Four-D worldview, as proposed by Thiagarajan and Semmel. The Microsoft Office-based computerized content learning offers intuitive learning through Microsoft Office that coordinates with the ELLMA learning administration framework. A test of 25 understudies at Politeknik Mitra Karya Mandiri was subjected to testing of the media amid the Learning Proses, which yielded positive acknowledgment comes about. The discoveries of this ponder propose that utilizing Microsoft Office-based computerized data is both practical and productive in upgrading understudy inspiration and making strides in learning results. This recommends that joining computerized learning into online instruction can be useful for directing college understudies. The approach is one of education, training, and practice as well as instruction and practice for 1st semester of information management students and 1st semester of Health Analyst at the Politeknik Mitra Karya Mandiri Ketanggungan Brebes. This mentoring activity received positive feedback from the target audience.